Distribution characteristics of stress and displacement of rings of cylindrical roller bearing. (June 2019) - Hao, Xu; Gu, Xinxin; Zhou, Xianwen; Liao, Xin; Han, Qingkai
In this paper, the developed finite element model of the shaft-cylindrical roller bearing–bearing housing system is established considering the temperature effect and clearance change. The displacement, raceway stress, and bearing stiffness characteristics of the inner and outer rings of the bearing are systematically investigated. The proposed finite element model is validated through adjusting mesh size of the bearing and the comparison of the elastic deformation of the bearing with the experiment. The influence of load, clearance, and temperature expansion on the displacement distribution of the inner and outer rings of the bearing, raceway stress, and stiffness characteristics are all discussed. The obtained results indicate that an appropriate selection of thermal expansion stress can obtain desirable working ambient temperature of the bearing under different clearances, which can serve as an efficient tool in the design of bearing parameters.